2021
DOI: 10.1002/pol.20210408
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating polymers within a single‐crystal: From heterogeneous structure to multiple functions

Abstract: Single-crystals, commonly considered as homogeneous solids, are able to be internally interfaced abnormally with guest polymers, which can be found in the biominerals where single-crystals incorporate surrounding biomacromolecules to reinforce their mechanical properties. This unique feature combining heterogeneous structure and long-range atomic ordering have attracted abundant investigations of reproducing their synthetic analogs to expand the potential application scope. Here, we summarize the recent progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 117 publications
(325 reference statements)
0
15
0
Order By: Relevance
“…Moreover, Li et al demonstrated that incorporation of conjugated polymer networks into C 60 single crystals can enhance their optoelectronic properties and incorporation of TiO 2 networks into PbI 2 crystals can improve X-ray detection sensitivity . In recent years, various amphiphilic diblock copolymer nanoparticles have been employed as crystal growth additives: this approach has produced a wide range of nanocomposite materials in which the guest organic nanoparticles are densely occluded within host inorganic crystals. Prior to these studies, Wegner et al pioneered the use of polymeric latexes as particulate additives for the mineralization of ZnO, demonstrating the successful incorporation of such particles . Similar results have been achieved using polymer-stabilized inorganic nanoparticles and even copolymer-stabilized oil droplets for other host crystals. It is remarkable that a wide range of hybrid materials can be designed using such a straightforward, efficient method. Unlike diblock copolymer nanoparticles, double-hydrophilic diblock copolymers are molecularly dissolved in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Li et al demonstrated that incorporation of conjugated polymer networks into C 60 single crystals can enhance their optoelectronic properties and incorporation of TiO 2 networks into PbI 2 crystals can improve X-ray detection sensitivity . In recent years, various amphiphilic diblock copolymer nanoparticles have been employed as crystal growth additives: this approach has produced a wide range of nanocomposite materials in which the guest organic nanoparticles are densely occluded within host inorganic crystals. Prior to these studies, Wegner et al pioneered the use of polymeric latexes as particulate additives for the mineralization of ZnO, demonstrating the successful incorporation of such particles . Similar results have been achieved using polymer-stabilized inorganic nanoparticles and even copolymer-stabilized oil droplets for other host crystals. It is remarkable that a wide range of hybrid materials can be designed using such a straightforward, efficient method. Unlike diblock copolymer nanoparticles, double-hydrophilic diblock copolymers are molecularly dissolved in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…To construct a uniform occlusion of dyes within an NLO single-crystal, instead of the anisotropic incorporation, an isotropic binding interaction that induces the incorporation process needs to be introduced into the crystallization condition. Interestingly, nonspecific binding interactions widely exist in the crystallization process within gel matrices. This is also inspired by the biomineralization process where the growing mineral crystals incorporate surrounding biomacromolecules. As a single crystal growing in a gel matrix, the interconnected gel-networks can withstand the crystallization pressure exerted from growing surfaces, leading to gel-incorporation and three-dimensional penetration of gel-networks throughout the entire single crystal . More importantly, nanoparticles , and microgels that are essentially incompatible with single crystals could be efficiently incorporated under the guidance of gel-networks.…”
mentioning
confidence: 99%
“…In combination with the gel-incorporation triggered isotropic dyeing structure, as well as the boosted dye contents inside the crystals, the dyeing mechanisms of a gel-grown KDP single crystal can be proposed. First, silica hydrogels have three-dimensionally irregular gel-networks with high specific surface area, which are full of hydroxyl groups. , Therefore, a large quantity of free dye molecules in the gel matrix are able to bind on the gel-networks by virtue of physical absorption or H-bonds, as evidenced by the PL quenching of dyes observed in gels. Second, when crystallization starts, the growing crystals isotropically incorporate the surrounding interconnected and dye-attached gel-networks, ensuring the isotropic dyeing of crystals.…”
mentioning
confidence: 99%
“…Although various nanoparticles have been encapsulated into MOFs, it remains a technical challenge to efficiently incorporate MOF crystals into inorganic single crystals during the crystallization of the latter in aqueous media. This is perhaps not surprising because crystallization normally favors the exclusion of impurities rather than their inclusion. In the present study, we sought to incorporate MOF nanoparticles into inorganic host crystals (CaCO 3 ). Our strategy involves the decoration of the MOF crystals with a suitable polymer to not only overcome the incompatibility between the guest MOF crystals and the host crystals, but also drive the efficient incorporation of MOF crystals into host crystals (Scheme ).…”
Section: Introductionmentioning
confidence: 99%